2014
DOI: 10.1111/cobi.12383
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the contribution of zoos and aquariums to Aichi Biodiversity Target 1

Abstract: The United Nations Strategic Plan for Biodiversity 2011-2020 is a key initiative within global efforts to halt and eventually reverse the loss of biodiversity. The very first target of this plan states that "by 2020, at the latest, people are aware of the values of biodiversity and the steps they can take to conserve and use it sustainably." Zoos and aquariums worldwide, attracting more than 700 million visits every year, could potentially make a positive contribution to this target. However, a global evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
111
2
17

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 130 publications
(133 citation statements)
references
References 22 publications
3
111
2
17
Order By: Relevance
“…We termed this variable "biodiversity definition." This is similar to the definition of biodiversity knowledge used by Moss et al (2014), although their measure had five steps. There were no differences between those on their way into the zoo and those on their way out in the accuracy of their biodiversity definition (t = 1.5, df = 170, p = .12).…”
Section: Preexisting Engagement With the Topicmentioning
confidence: 99%
See 3 more Smart Citations
“…We termed this variable "biodiversity definition." This is similar to the definition of biodiversity knowledge used by Moss et al (2014), although their measure had five steps. There were no differences between those on their way into the zoo and those on their way out in the accuracy of their biodiversity definition (t = 1.5, df = 170, p = .12).…”
Section: Preexisting Engagement With the Topicmentioning
confidence: 99%
“…Besides their direct conservation mission, they devote attention and effort to environmental education (http://www.waza.org/en/site/about-waza/wha t-we-do; Khalil and Ardoin 2011). Indeed, research has shown that zoo visits can increase knowledge (Falk et al 2007;Khalil and Ardoin 2011;Moss et al 2014). A recent worldwide survey of over 6000 participants found an increase in biodiversity understanding as well as awareness of actions that could be taken to protect biodiversity from the beginning to the end of the zoo visit (Moss et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Particularmente, en el abordaje del concepto biodiversidad en espacios no formales de educación, una investigación realizada con 5561 visitantes de 26 zoológicos distribuidos en 19 países (Moss, Jensen, Gusset, 2014) reportó que después de visitar el Zoológico y participar de sus propuestas educativas, los visitantes incrementan su entendimiento sobre lo que es biodiversidad, así como sus conocimientos sobre acciones para contribuir en su protección.…”
Section: Procesos De Enseñanza Y Aprendizaje En Zoológicosunclassified